(untitled) (Journal of Pathology of Nepal, 2021)
Background: Anemia being the expression of the underlying disease is a global public health problem affecting both developing as well as developed countries. The RBC indices and platelet count variation among anemic patients are important to know their association for clinical implications. Materials and Methods: A hospital-based cross-sectional study among anemic patients with hemoglobin <10 gm%, attending Birat Medical College Teaching Hospital, Nepal from 15 May to 15 July 2020 were analyzed for RBC indices and platelet count variation. Demographic data, RBC indices, platelet count variation, and types of anemia were evaluated. Pearson’s correlation coefficient was used for correlating the platelet count with RBC indices. A Chi-square test was used to know about the association between the types of anemia and platelet count variation. Results: Out of 150 anemic patients, the female to male ratio was 1.5:1, with the most common age group between 40-49 years. There exist high differences between minimum and maximum individual RBC indices (Hb, MCV, MCH, MCH) and platelet count values. The platelet count variation with RBC values and MCV had a statistically significant positive and negative correlation respectively. However, the correlation between platelet count variation with hemoglobin concentration level and type of anemia was positive but statistically not significant. Conclusion: Findings suggest that platelet count variation with RBC indices and types of anemia correlated well among anemic patients. Such association will enable the clinicians for diagnosing and treatment purposes.